2016
DOI: 10.4103/0974-9233.194077
|View full text |Cite
|
Sign up to set email alerts
|

Bottle characteristics of topical international glaucoma medications versus local brands in Saudi Arabia

Abstract: WHAT IS KNOWN AND OBJECTIVE:Physical bottle characteristics differ of brand name topical glaucoma medications and local generic equivalents. This study compares the bottle characteristics of international topical glaucoma brands versus local brands from the Kingdom of Saudi Arabia.METHODS:Data were collected on bottle drum volume, drop volume, bottle squeezability, bottle tip diameter, labels and instructions, cap color coding, and clarity of the drug label. Density-based calculations of drops in bottle volume… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
1
2
0
Order By: Relevance
“…A 2016 study of various medications, including five brands common in the United States, showed that for 2.5 mL and 5 mL bottles of latanoprost, the average number of drops per bottle using the stock bottle dropper was between 83.3–85.3 and 127.7–163.3, respectively. 20 Similarly, our data show that a 2.5 mL bottle contains between 54 and 97 drops per bottle. The large variation in number is likely because emulsions and suspensions tend to create larger drop volumes and were included along with solutions in our study.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…A 2016 study of various medications, including five brands common in the United States, showed that for 2.5 mL and 5 mL bottles of latanoprost, the average number of drops per bottle using the stock bottle dropper was between 83.3–85.3 and 127.7–163.3, respectively. 20 Similarly, our data show that a 2.5 mL bottle contains between 54 and 97 drops per bottle. The large variation in number is likely because emulsions and suspensions tend to create larger drop volumes and were included along with solutions in our study.…”
Section: Discussionsupporting
confidence: 67%
“…Additionally, the bottle volume and number of drops per bottle varied in our study, which is consistent with reported deviations between true and stated bottle volumes. 20 …”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the diameters of the vial tips differed significantly. A patient survey revealed that local brand vials were easier to squeeze, which is an important factor for users who struggle with compression force (31,32). Changing the type of vial used can result in a decrease in the dosed volume, which has both economic and biopharmaceutical implications.…”
Section: Multidose Ampoulesmentioning
confidence: 99%